Health professionals’ knowledge and attitudes towards baby led weaning: A cross-sectional, exploratory, and observational study - Paula Sarreira-de-Oliveira; Renata Ramalho; Ricardo Antunes; Vanessa Antunes; Fernanda Loureiro (PLoS ONE, 2026)
Baby Led Weaning (BLW) is a type of infant feeding that allows babies to feed themselves and has gain popularity among parents in recent years. Health professionals’ (HP) knowledge and attitudes towards BLW is less explored. We conducted a cross-sectional, exploratory, and observational study, with a web-based instrument, that aimed to determine the knowledge and attitudes of HP familiar to BLW regarding the use of this method in complementary feeding. In our sample of 118 HP, HP who were women or younger (23–39 years) had a more positive perception of BLW. We found that acceptance and positive attitudes towards BLW were consistent among HP. It is essential to improve the training of HP in the specifics of implementing this approach and to develop clear guidelines to guide practice.